Ni2+-doped ZnxCd1−xS photocatalysts from single-source precursors for efficient solar hydrogen production under visible light irradiation - Wang, Yabo (2013)
Ni2+-doped photocatalysts Ni(y)-ZnxCd1−xS (where 0 ≤ x ≤ 0.80, 0% ≤ y ≤ 8%) were prepared by a two-step route, which consisted of a first precipitation of single-source precursors and a subsequent solvothermal treatment of the precursors in ethylenediamine. Structural, morphological and optical properties of the as-prepared samples were characterized by XRD, UV-vis DRS, FESEM, TEM, N2 physisorption, ICP-AES and XPS techniques. The photocatalytic activity was evaluated for hydrogen evolution from the aqueous solution containing sodium sulfide and sodium sulfite under visible light irradiation. All Ni2+-doped samples exhibit enhanced photocatalytic activity compared with the non-doped sample. Sample Ni(4%)-Zn0.4Cd0.6S gives the highest hydrogen evolution rate of 941 μmol h−1 under the optimized reaction conditions without any co-catalysts, with a corresponding quantum efficiency of 22.8% at 420 nm which is much higher compared to those of previously reported Ni2+-doped metal sulfide photocatalysts. It is suggested that good crystallinity, suitable band structure and the accommodation sites introduced by Ni2+ doping for charge carrier separation together contribute to the high activity of such photocatalysts for hydrogen evolution.